Sero-Epidemiology of Foot and Mouth Disease in Domestic Ruminants in Amhara Region, Ethiopia - Mesfine, Mekedes; Nigatu, Seleshe; Belayneh, Negus; Jemberu, Wudu T. (Frontiers in Veterinary Science, 2019)
Abstract This study involved cross-sectional serological and questionnaire surveys to investigate the seroepidemiology of foot and mouth disease (FMD) in domestic ruminants and farmers’ knowledge and practices about the disease in Amhara region of Ethiopia. A multistage cluster sampling was carried out to select domestic ruminants for serological sampling and farmers for interview. A total of 1672 sera samples were collected and tested using 3ABC-Enzyme Linked Immunosorbent Assay, and 170 farmers were interviewed. An overall FMD seroprevalence of 11.48% was recorded in the domestic ruminants. The seroprevalence of FMD was higher in cattle (14.37%) than goats (7.10%) and sheep (7.07%). The age stratified seroprevalence in the districts showed that 66.67% of the study districts experienced FMD outbreak within the preceding one year of this study time. A mixed effect logistic regression analysis revealed, agroecology, production system, age of animal, and history of FMD infection were significantly associated with FMD seropositivity in cattle (P<0.05). A statistically significant (P<0.05) positive correlation (r = 0.93) was observed between cattle and small ruminants FMD seroprevalences. About 82 % of farmers interviewed described a consistent and valid clinical picture of FMD and 85% of them had the experience of the disease in their herds. The farmers mostly employ traditional means of disease control. In conclusion, findings of the study indicated that FMD is an important disease in Amhara region more importantly in intensive production system and lowlands parts of the region. High correlation in seroprevalence between small and large ruminants indicated possible cross transmission between these species. Despite good knowledge about the disease, farmers deal with FMD only when it occurs through traditional treatment of affected animals. An organized control of the disease through vaccination and animal movement is needed to control and reduce the disease’s impact on farmers’ livelihood and the region’s economy.